2004
DOI: 10.1080/0265053042000314401
|View full text |Cite
|
Sign up to set email alerts
|

Inside–out: Resocialisation From Prison as a Biographical Process. A Longitudinal Approach to the Psychodynamics of Imprisonment1

Abstract: a a PhD, is Senior Researcher at the Criminological Research Institute of Lower Saxony (KFN) , Hannover and teaches Sociology at the University of Hannover, KFN ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…In addition, Kazemian (2007) reminds us of the meaning of situational temptations and opportunities. High selfefficacy and trust in one's own options would on the contrary rather contribute to stable behaviour patterns (Bereswill, 2004;Mulvey et al, 2004). These insights are supported by my previous research that found formerly delinquent immigrants quite quickly desist from former behaviour after arrival, if their agency and motivation are acknowledged and if they receive sufficient support from new inmates and institutions that have been known to regularly compensate for lack of support from the family in the first period after immigration (Zdun, 2012).…”
supporting
confidence: 54%
See 3 more Smart Citations
“…In addition, Kazemian (2007) reminds us of the meaning of situational temptations and opportunities. High selfefficacy and trust in one's own options would on the contrary rather contribute to stable behaviour patterns (Bereswill, 2004;Mulvey et al, 2004). These insights are supported by my previous research that found formerly delinquent immigrants quite quickly desist from former behaviour after arrival, if their agency and motivation are acknowledged and if they receive sufficient support from new inmates and institutions that have been known to regularly compensate for lack of support from the family in the first period after immigration (Zdun, 2012).…”
supporting
confidence: 54%
“…Moreover, although we know that in many countries prison systems are often far from being 'machines of resocialization', youth prisons bear at least a certain potential for clear-cut shifts (Maruna, 2001;Bereswill, 2004). This requires a supportive environment but particularly personal readiness to change.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In what follows, biography is approached from a psychoanalytical perspective as a ‘multi‐layered synthesis; a synthesis of conscious and unconscious impulses and past and present experiences’ (Bereswill 2004a, p.14; cf. Bereswill 2007; Gadd and Jefferson 2007; Koesling and Neuber 2007).…”
Section: A Conflict‐oriented Model Of Biographymentioning
confidence: 99%